Synthesis and Characterization of Organic Dyes with Various Electron‐Accepting Substituents for p‐Type Dye‐Sensitized Solar Cells. Issue 11 (18th September 2014) - Weidelener, Martin; Powar, Satvasheel; Kast, Hannelore; Yu, Ze; Boix, Pablo P.; Li, Chen; Müllen, Klaus; Geiger, Thomas; Kuster, Simon; Nüesch, Frank; Bach, Udo; Mishra, Amaresh; et al.
Abstract Four new donor‐π‐acceptor dyes differing in their acceptor group have been synthesized and employed as model systems to study the influence of the acceptor groups on the photophysical properties and in NiO‐based p‐type dye‐sensitized solar cells. UV/Vis absorption spectra showed a broad range of absorption coverage with maxima between 331 and 653 nm. Redox potentials as well as HOMO and LUMO energies of the dyes were determined from cyclic voltammetry measurements and evaluated concerning their potential use as sensitizers in p‐type dye‐sensitized solar cells (p‐DSCs). Quantum‐chemical density functional theory calculations gave further insight into the frontier orbital distributions, which are relevant for the electronic processes in p‐DSCs. In p‐DSCs using an iodide/triiodide‐based electrolyte, the polycyclic 9, 10‐dicyano‐acenaphtho[1, 2‐b]quinoxaline (DCANQ) acceptor‐containing dye gave the highest power conversion efficiency of 0.08 %, which is comparable to that obtained with the perylenemonoimide (PMI)‐containing dye. Interestingly, devices containing the DCANQ‐based dye achieve a higher VOC of 163 mV compared to 158 mV for the PMI‐containing dye. The result was further confirmed by impedance spectroscopic analysis showing higher recombination resistance and thus a lower recombination rate for devices containing the DCANQ dye than for PMI dye‐based devices. However, the use of the strong electron‐accepting tricyanofurane (TCF) group played a negative role in the device performance, yielding an efficiency of only 0.01 % due to a low‐lying LUMO energy level, thus resulting in an insufficient driving force for efficient dye regeneration. The results demonstrate that a careful molecular design with a proper choice of the acceptor unit is essential for development of sensitizers for p‐DSCs.